2017
DOI: 10.3393/ac.2017.33.2.46
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic Versus Biological Mesh-Related Erosion After Laparoscopic Ventral Mesh Rectopexy: A Systematic Review

Abstract: PurposeThis review reports the incidence of mesh-related erosion after ventral mesh rectopexy to determine whether any difference exists in the erosion rate between synthetic and biological mesh.MethodsA systematic search of the MEDLINE and the Ovid databases was conducted to identify suitable articles published between 2004 and 2015. The search strategy capture terms were laparoscopic ventral mesh rectopexy, laparoscopic anterior rectopexy, robotic ventral rectopexy, and robotic anterior rectopexy.ResultsEigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
6
30
0
1
Order By: Relevance
“…The senior author maintains that a non‐absorbable suture should be used to suture Permacol to the rectum because (i) the incorporation time for Permacol is > 15 months, (ii) the absorption time for PDS ® is 182−238 days and (iii) the rectum is 2−3 mm thicker than the vagina and therefore less susceptible to suture‐related morbidity. These results are in accordance with other published results on LVMR using biological mesh . In contrast, synthetic mesh‐related morbidity after LVMR has been reported as 1.1% (polypropylene), 3.3% (polyester) , 2.4% (various) and 4.6% (Marlex or polypropylene) (10‐year Kaplan–Meier estimate) .…”
Section: Discussionsupporting
confidence: 91%
“…The senior author maintains that a non‐absorbable suture should be used to suture Permacol to the rectum because (i) the incorporation time for Permacol is > 15 months, (ii) the absorption time for PDS ® is 182−238 days and (iii) the rectum is 2−3 mm thicker than the vagina and therefore less susceptible to suture‐related morbidity. These results are in accordance with other published results on LVMR using biological mesh . In contrast, synthetic mesh‐related morbidity after LVMR has been reported as 1.1% (polypropylene), 3.3% (polyester) , 2.4% (various) and 4.6% (Marlex or polypropylene) (10‐year Kaplan–Meier estimate) .…”
Section: Discussionsupporting
confidence: 91%
“…Complete rectal prolapse (CRP) is defined as full-thickness protrusion of the rectal wall through the anus 1 . It begins as intussusception (IS) which may or may not be symptomatic 2 .…”
Section: Introductionmentioning
confidence: 99%
“…25 A more recent systematic review looking at mesh erosion found there was a significantly lower incidence of mesh erosion in the biologic mesh group (0.22%) when compared with the synthetic mesh group (1.87%). 26 However, there was variability in the included studies regarding study type, length of follow-up, and type of mesh used. Further studies are needed to determine which type of mesh is safer and is associated with lower recurrence rates.…”
Section: Choice Of Meshmentioning
confidence: 99%